Kualitas Air Muara Sungai Batang Arau (Muara Padang) Sumatera Barat - Wike Ayu Eka Putri (Faculty of Mathtmatics and Natural Sciences, 2008)
Batang Arau River and Muara Padang has many activities of human being such as agriculture, resident, hospital and anchorage. At the end, this condition will disturb biota lifecycle and environment esthetics. In fact, goverment of Padang Town has planned Muara Padang as a center of tourism in Padang. The purpose of this research is to find information about water quality of Muara Padang. The pasut type of Muara Padang is semudual tides, salinity value when high tides more than low tides. The water quality parameter analysis (TSS, DO, COD, NO3, NO2, NH3 and PO4) indicated that Batang Arau Rives (Station 1 and 2) was polluted because not sutable with waters quality standart (Base on Kepmen No. 51/MENLH/2004 and PP RI No. 82 2001). Water quality at estuaries and sea area (Station 3,4,5,6 and 7) still good and supported of life organisms in this area.